Predictors of Individuals’ Behavioral Characteristics of Routine Activities Theory: Analysis of a Synthesis Model of Socio-Economic Status, Victimization, and Fear of Crime - Choi, Jisun; Jung, Heesoo (International Journal of Criminology and Sociology, 2021)
Researchers have studied victimization, fear of crime, and individuals’ behavioral characteristics to investigate the origin of crime and victimization, such as the routine activity theory. However, little research has examined how the behavioral characteristics were formed in theory. Although the elements of socioeconomic status, victimization experience, and fear of crime are believed to cause differences in human behaviors, the current study attempts to examine which predictors construct behavior characteristics like the routine activity theory, including target suitability and guardianship. Using the most recent, nationally collected official crime victimization data from South Korea (Korean Crime Victimization Survey, 2014), the study analyzed the variables with statistical models. The results suggest the following:(1) an individual’s socioeconomic status – such as gender, age, and education level – rather than victimization experience or fear of crime, are significant predictors of target suitability;(2) higher levels of fear of crime predict higher levels of guardianship; and (3) the victimization experience did not predict either target suitability or guardianship.